Efficient residual network using hyperspectral images for corn variety identification - Li, Xueyong; Zhai, Mingjia; Zheng, Liyuan; Zhou, Ling; Xie, Xiwang; Zhao, Wenyi; Zhang, Weidong (Frontiers in Plant Science, 2024)
Corn seeds are an essential element in agricultural production, and accurate identification of their varieties and quality is crucial for planting management, variety improvement, and agricultural product quality control. However, more than traditional manual classification methods are needed to meet the needs of intelligent agriculture. With the rapid development of deep learning methods in the computer field, we propose an efficient residual network named ERNet to identify hyperspectral corn seeds. First, we use linear discriminant analysis to perform dimensionality reduction processing on hyperspectral corn seed images so that the images can be smoothly input into the network.Second, we use effective residual blocks to extract fine-grained features from images. Lastly, we detect and categorize the hyperspectral corn seed images using the classifier softmax. ERNet performs exceptionally well compared to other deep learning techniques and conventional methods.With 98.36% accuracy rate, the result is a valuable reference for classification studies, including hyperspectral corn seed pictures.